2006
DOI: 10.3168/jds.s0022-0302(06)72580-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytes in Bovine Prepartum Mammary Secretions and Their Usefulness for Predicting Parturition

Abstract: Accurately predicting parturition in cows can be difficult because of the variability in gestation length and uncertainty of the time of parturition. The goal of the present study was to determine the electrolyte concentrations of prepartum mammary secretions of gravid cows and to investigate retrospectively the possible predictive relationships between these concentrations and the time of parturition. Twenty-three cows were sampled once daily for 3 to 12 d before they calved. The concentrations of calcium, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 6 publications
0
11
0
1
Order By: Relevance
“…Previously proposed protocols [8-15] allow the start of calving to be predicted within a window of several hours and also require frequent monitoring of cows. In contrast, the system employed in this study gave an accurate determination of the beginning of the second stage of labour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously proposed protocols [8-15] allow the start of calving to be predicted within a window of several hours and also require frequent monitoring of cows. In contrast, the system employed in this study gave an accurate determination of the beginning of the second stage of labour.…”
Section: Discussionmentioning
confidence: 99%
“…To predict the exact moment at which the calving process begins, various protocols have been proposed including ultrasound monitoring [8], observing changes in the body temperature [9-11], analysing blood levels of oestrone sulphate and 17-β-oestradiol [12], evaluating blood levels of progesterone [13], controlling the level of relaxation of pelvic ligaments [14], determining the concentration of electrolytes present in mammary gland secretions [15] and, lastly, video monitoring the animals [16]. …”
Section: Introductionmentioning
confidence: 99%
“…Studies on Holstein cows have shown that calving complications cause reduced reproductive performance, resulting in a longer period between calving and conception (Dematawewa and Berger 1997). Various protocols have been proposed to determine the exact moment during which the calving process begins, including ultrasound monitoring (Wright et al 1988), observing changes in body temperature (Fujomoto et al 1988;Aoki et al 2005), analyzing blood levels of estrone sulfate and 17-ß-estradiol (Shah et al 2007), analyzing blood levels of progesterone (Matsas et al 1992), controlling the level of relaxation of pelvic ligaments (Dufty 1971), and determining the concentration of electrolytes present in mammary gland secretions (Bleul et al 2006). Recently, a proposal was made regarding the use of an electronic system that once attached to the vulva, gets activated by expulsion of fetal membranes, thus, generating a radio-wave frequency that is transmitted to the global system for mobile communications (GSM).…”
Section: Introductionmentioning
confidence: 99%
“…The prediction of parturition in cattle has been investigated using real-time ultrasound (Wright et al, 1988), changes in body temperature (Burfeind et al, 2011), blood 17-β-estradiol (Shah et al, 2007) or progesterone profile (Matsas et al, 1992), relaxation of pelvic ligament (Dufty, 1971), electrolyte concentration in mammary secretions (Bleul et al, 2006), intravaginal insert devices that are activated when pushed out of the vagina by the AS (Palombi et al, 2013), and video monitoring of cows before calving (Cangar et al, 2008). The technology to monitor physical cow activity for reproduction (Aungier et al, 2012;Kamphuis et al, 2012;Chebel et al, 2013) or rumination (Reith and Hoy, 2012) as well as health events (e.g., locomotion; Chapinal et al, 2011) are management tools available for dairy herds.…”
mentioning
confidence: 99%